Pathways to coexistence with dingoes across Australian farming landscapes - Boronyak, Louise; Jacobs, Brent (Frontiers in Conservation Science, 2023)
Agriculture and biodiversity conservation are both vitally important human activities that overlap geographically and are often in conflict. Animal agriculture has been implicated in species loss and the degradation of ecosystems due to land clearing, overgrazing, and conflicts with large carnivores such as dingoes (Canis dingo). This paper explores the potential for transformation in Australian commercial livestock production from human-dingo conflict towards social-ecological coexistence. A qualitative model that depicts transformative change was developed from field observations and twenty-one in-depth interviews with livestock producers, conservation researchers, grazing industry representatives and policy makers across Australia. The model articulates the current state of dingo management and the drivers of system change. Seven pathways are described to catalyse transformation from routine lethal management of dingoes towards a future vision that embeds mutually beneficial coexistence. Central to transformation is the adoption by livestock producers of preventive non-lethal innovations supported by a new farming movement, Predator Smart Farming, that balances livestock grazing and wildlife conservation values to unlock the resilience of landscapes, animals (domesticated and wild) and livelihoods. Other key pathways are discussed that include targeted research, capacity building, outreach and knowledge sharing networks; institutional (policy, legislation, and economic incentives) and cultural change; public awareness raising and advocacy to reduce lethal control; and greater involvement of Indigenous Australians in decisions relating to wildlife management. These findings have implications for coexistence with large carnivores in rangeland ecosystems globally.